Virological Response in Cerebrospinal Fluid to Antiretroviral Therapy in a Large Italian Cohort of HIV-Infected Patients with Neurological Disorders. (26th August 2012) - Giancola, Maria Letizia; Lorenzini, Patrizia; Cingolani, Antonella; Baldini, Francesco; Bossolasco, Simona; Bini, Teresa; Monno, Laura; Picchi, Giovanna; d'Arminio Monforte, Antonella; Cinque, Paola; Tozzi, Valerio; Antinori, Andrea
Abstract : The aim of the present study was to analyse the effect of antiretroviral (ARV) therapy and single antiretroviral drugs on cerebrospinal fluid (CSF) HIV-RNA burden in HIV-infected patients affected by neurological disorders enrolled in a multicentric Italian cohort. ARVs were considered "neuroactive" from literature reports. Three hundred sixty-three HIV-positive patients with available data from paired plasma and CSF samples, were selected. One hundred twenty patients (33.1%) were taking ARVs at diagnosis of neurological disorder. Mean CSF HIV-RNA was significantly higher in naïve than in experienced patients, and in patients not taking ARV than in those on ARV. A linear correlation between CSF HIV-RNA levels and number of neuroactive drugs included in the regimen was also found (r = − 0.44, P < 0.001 ). Low -plasma HIV-RNA and the lack of neurocognitive impairment resulted in independently associated to undetectable HIV-RNA. Taking nevirapine or efavirenz, or regimen including NNRTI, NNRTI plus PI or boosted PI, was independently associated to an increased probability to have undetectable HIV-RNA in CSF. The inclusion of two or three neuroactive drugs in the ARV regimen was independently associated to undetectable viral load in CSF. Our data could be helpful in identifying ARV regimens able to better control HIV replication in the CNS sanctuary, and could be a historical reference for further analyses.